Membrane electrode assembly and fuel cell
By introducing a third catalyst that can catalyze CO oxidation into CO2 into the anode of the membrane electrode assembly, the problem of insufficient CO tolerance in existing fuel cells is solved, high catalytic activity and high CO tolerance are achieved, and the power density and stability of the fuel cell are improved.
Patent Information
- Application Number
- CN202080053912.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-26
- Filing Date
- 2020-07-10
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-07-10
AI Technical Summary
The membrane electrode assembly in existing fuel cells has low tolerance to carbon monoxide (CO), resulting in a decrease in catalyst activity and a decrease in fuel cell efficiency.
A membrane electrode assembly is designed, including a cathode, anode and a proton conductive membrane. The cathode and anode contain metal catalysts and proton conductive ionomers respectively, and a third catalyst that can catalyze CO oxidation into CO2 is introduced into the anode to improve CO tolerance.
High catalytic activity and high CO tolerance are achieved, the power density and long-term stability of fuel cells are improved, and the toxic effect of CO on catalyst activity is reduced.
Smart Images

Figure CN114175319B_ABST
Abstract
Description
[0001] The present invention relates to a membrane electrode assembly having high catalytic activity while having improved carbon monoxide (CO) tolerance and a fuel cell including such a membrane electrode assembly.
[0002] Membrane-electrode assemblies for fuel cell applications are known from the prior art, which membranes are coated with an anode on one side and a cathode on the other side. The anode usually contains platinum as a catalyst, which catalytically converts the hydrogen fed into the fuel cell into protons. Platinum is also usually used as a catalyst for reducing oxygen on the cathode side. A disadvantage of previous membrane-electrode assemblies is their low tolerance to CO, which acts as a catalyst poison and also reduces the efficiency of the membrane-electrode assembly and thus also the fuel cell.
[0003] It is an object of the present invention to provide a membrane electrode assembly which is distinguished by a high catalytic activity and also a high CO tolerance. Furthermore, it is an object of the present invention to provide a fuel cell having a permanently high power density.
[0004] This object is achieved by the features of the independent claim. The dependent claims contain advantageous developments of the invention.
[0005] Therefore, the object is achieved by a membrane electrode assembly, the membrane electrode assembly comprising a cathode, an anode and a proton conducting membrane. The membrane is arranged between the cathode and the anode. The cathode comprises a first metal-containing catalyst and a proton conducting ionomer. The first catalyst is preferably uniformly distributed in the ionomer so that a high catalytic activity is generated over the entire cathode and oxygen is effectively converted. In particular, the first catalyst is limited to, the first catalyst catalyzes the cathode reaction, i.e., the reduction of oxygen.
[0006] The anode also includes a proton-conducting ionomer and further includes a metal-containing second catalyst that catalyzes the oxidation process of hydrogen to protons. In other words, the second catalyst catalyzes the anode reaction, i.e., the conversion (oxidation) of hydrogen to protons. The protons then migrate through the proton-conducting membrane and subsequently react with the reduced oxygen.
[0007] In addition, the anode also includes a catalyst for converting CO to CO 2 The third catalyst contains a metal that is used for the reaction of CO (i.e., the oxidation of CO). CO, which acts as a catalyst poison and reduces the electrode efficiency, may be introduced, for example, by hydrogen-containing combustion gases. If it is not removed quickly, it will block the active sites of the catalyst and significantly reduce the power density of the membrane electrode assembly. By providing a third catalyst, the existing CO is oxidized to CO 2 And thus rendered harmless. 2The efficiency of the catalyst is not impaired, thereby improving the tolerance to CO by the third catalyst. The ratio of the total mass ratio of the platinum of the second catalyst and the platinum of the third catalyst to the total mass ratio of the metal other than platinum of the second catalyst and the third catalyst is greater than 3: 1. With this mass ratio, a high long-term stability of the power density is first achieved in the membrane electrode assembly of the present invention and a high CO tolerance is achieved at the same time.
[0008] As the first, second and third metal-containing catalysts, those metal-containing catalysts that catalyze the corresponding desired reaction and contain at least one metal can be considered. The metal can exist in different forms here. Exemplary catalysts include (pure, i.e., simple) metals, such as noble metals, and Ir, Ru and Pt therein, but also metal oxides and alloys of two or more metals. The second and third catalysts can contain the same metal, but exist in different forms. Thus, for example, the second catalyst is a (pure) metal, and the third catalyst is an alloy. Or the second catalyst is a (pure) metal, and the third catalyst is a metal oxide. Or the second catalyst is a metal oxide, and the third catalyst is an alloy. Any combination of metal-containing catalysts in the second and third catalysts is possible.
[0009] The mass ratio is determined based on the corresponding mass of the metal of the corresponding metal-containing catalyst. Here, the second catalyst or the third catalyst or the second catalyst and the third catalyst may contain platinum. It is not necessary for both the second catalyst and the third catalyst to contain platinum, as long as the mass ratio of the total mass of platinum in the second catalyst and the third catalyst to the total mass of the remaining metals (i.e., all metals except platinum) in the second catalyst and the third catalyst is greater than 3:1.
[0010] According to the present invention, the total weight per unit area of the platinum of the second catalyst and the platinum of the third catalyst is less than 0.4 mg / cm 2 , thus achieving very good catalytic performance with minimal economic cost.
[0011] The CO tolerance can be advantageously improved while the membrane electrode assembly has very good power density as follows: the ratio of the total mass ratio of the platinum of the second catalyst and the platinum of the third catalyst to the total mass ratio of the metal other than platinum of the second catalyst and the third catalyst is less than or equal to 9:1.
[0012] According to another advantageous improvement, the second catalyst and the third catalyst are arranged on a conductive carrier, respectively. The conductive carriers on which the second catalyst and the third catalyst are arranged can be the same conductive carrier, respectively, or different conductive carriers can be used. The conductivity of the anode can be improved thereby, which is beneficial to the power density of the membrane electrode assembly. The second catalyst and / or the third catalyst can be present as separate electrode layers or evenly distributed in a common electrode layer. In the former case, the following layer sequence is obtained for the membrane electrode assembly: cathode / membrane / anode layer 1 / anode layer 2. In the latter case, the following layer sequence is obtained for the membrane electrode assembly: cathode / membrane / anode.
[0013] Due to the very high reactivity and thus good catalytic properties, the second catalyst and the third catalyst are selected from alloys, metals, metal oxides or mixtures of these compounds. Here, at least one of these metal-containing compounds of the second catalyst and / or the third catalyst contains platinum, so that the ratio of the total mass of the platinum of the second catalyst and the platinum of the third catalyst to the total mass ratio of the metal other than platinum of the second catalyst and the third catalyst is set to be greater than 3:1. The second catalyst is preferably platinum. It is further advantageous that the third catalyst is a platinum alloy, because the platinum alloy can be selected very well with respect to CO binding and conversion activity.
[0014] The alloy particularly advantageously comprises platinum and at least one element selected from the group consisting of Ru, Rh, Ni, Cu and Ir. Of the above alloying elements, Ru is particularly preferred because it not only binds CO very quickly and thus efficiently but also promotes the transfer of CO to the 2 conversion.
[0015] It is further advantageous if the conductive support is selected from conductive carbon, inorganic oxides and mixtures thereof. Due to simplified processing, conductive carbon or one or more oxides are particularly advantageously used.
[0016] It is further advantageous if the electrically conductive carrier has a thickness of 50 to 1000 m 2 / g specific surface area, because thereby the second catalyst and the third catalyst can be particularly finely and evenly distributed in the anode. This improves the activity of the anode due to the increase in the binding sites for the catalytic reaction on the catalyst. The specific surface area is determined here by means of nitrogen adsorption (BET method) according to DIN ISO 9277:2003-05 "Determination of the specific surface area of solids by gas adsorption according to the BET method".
[0017] Another advantageous improvement is that the weight per unit area of platinum of the second catalyst is less than 0.3 mg / cm 2The weight per unit area of platinum is understood to be the weight of the platinum of the second catalyst relative to the geometric area of the anode facing the diaphragm. 2 The weight per unit area of platinum of the second catalyst can be kept as low as possible at a very high anodic catalytic activity.
[0018] In order to simultaneously achieve very good catalytic performance, the total weight per unit area of the platinum of the second catalyst and the platinum of the third catalyst is advantageously greater than 0.015 mg / cm 2 And especially greater than 0.03 mg / cm 2 .
[0019] For the above reasons, it is further preferred that the weight per unit area of platinum of the second catalyst is greater than 0.015 mg / cm 2 And especially greater than 0.03 mg / cm 2 .
[0020] In order to achieve a particularly high long-term stability of the performance of the membrane electrode assembly (i.e. a very high catalytic activity in the conversion of the fuel used) and very good CO tolerance, the mass ratio of the platinum of the first catalyst to the total mass ratio of the metals other than platinum of the second catalyst and the third catalyst is preferably greater than 12:1, in particular greater than 35:1. This ratio allows high power densities to be maintained over the long term even when alloy metals (e.g. ruthenium) are transferred from the anode to the cathode during operation. This process can lead to a reduction in the catalytic activity of the cathode, which is then less pronounced when the catalyst ratios described above are maintained.
[0021] Due to the very good catalytic activity in converting oxygen and protons into water, the first catalyst is advantageously selected from platinum, platinum alloys, transition metals, transition metal alloys and mixtures thereof.
[0022] In order to achieve as uniform a distribution as possible at low catalyst concentrations and thus very high cathode catalytic activity, according to another advantageous refinement, the first catalyst is arranged on a conductive support. As conductive supports, those conductive supports which have been described as advantageous for the second and third catalysts can be used.
[0023] If a transition metal alloy is used as the first catalyst, the transition metal alloy is in particular selected from platinum and cobalt. Platinum-cobalt alloys have proven to be readily available and have a high catalytic activity.
[0024] According to the present invention, a fuel cell comprising the membrane electrode assembly disclosed above is also described. Due to the use of the membrane electrode assembly of the present invention, a fuel cell having a durable high power density and being tolerant to CO can be realized.
[0025] The advantages, beneficial effects and improvements described for the membrane electrode assembly of the present invention also apply to the fuel cell of the present invention.
[0026] Further details, advantages and features of the invention are apparent from the following description of exemplary embodiments with the aid of the accompanying drawings. In the drawings:
[0027] Figure 1 A membrane electrode assembly according to one embodiment is shown in cross-section,
[0028] Figure 2 shows graphs illustrating test results regarding power stability and CO stability,
[0029] Figure 3 Showing the clarification from Figure 2 Table of test results on power stability, and
[0030] Figure 4 A table illustrating test results from the graph regarding CO stability is shown.
[0031] exist Figure 1 Only the key features of the membrane electrode assembly are shown. All other features are omitted for the sake of brevity.
[0032] Figure 1 A membrane electrode assembly 1 is shown, which comprises a cathode 2 and an anode 3 with a proton-conducting membrane 4 in between. The anode 3 is here the electrode at which hydrogen is oxidized to protons, which then react further to form water. The cathode 2 is the electrode at which oxygen is reduced.
[0033] The cathode 2 comprises a first catalyst 5 and a proton-conducting ionomer 6 , wherein the first catalyst 5 catalyzes the reduction of oxygen and comprises, in particular, platinum, a platinum alloy, one or more transition metals or mixtures thereof. The first catalyst is preferably arranged on an electrically conductive support 7 .
[0034] The anode 3 also includes a proton-conducting ionomer 8, a second catalyst 9 that catalyzes the reaction of hydrogen to protons, and a second catalyst 9 that catalyzes the reaction of CO to CO. 2 The second catalyst 9 and the third catalyst 10 are supported on a conductive carrier 11, respectively.
[0035] The second catalyst 9 is platinum, and the third catalyst 10 is a platinum alloy. In the platinum alloy, platinum constitutes a main component in mass % and at least one element selected from the group consisting of Ru, Rh, Ni, Cu and Ir is used as a doping element.
[0036] The ratio of the total mass ratio of platinum of the second catalyst 9 and platinum of the third catalyst 10 to the total mass ratio of metals other than platinum of the second catalyst 9 and the third catalyst 10 is greater than 3:1 and less than 10:1.
[0037] The unique features of the membrane electrode assembly 1 are the long-term stability of the very high power density and the very high tolerance to CO.
[0038] The following experiments were also conducted. A membrane electrode assembly having a cathode and an anode was prepared, wherein the cathode comprises 0.40 mg of Pt / cm 2 The anode also includes a proton-conducting ionomer having an ion exchange capacity of about 1.27 meq / g, a metal-containing second catalyst catalyzing the reaction of hydrogen to protons, and a metal-containing second catalyst catalyzing the reaction of CO to CO. 2 A third catalyst containing metal for the reaction of . Platinum is used as the second catalyst, and a platinum-ruthenium alloy is used as the third catalyst.
[0039] In the prepared membrane electrode assembly, the ratio of the total mass ratio of platinum of the second catalyst and platinum of the third catalyst (here 57.4 mass %) to the total mass ratio of metal (Ru) other than platinum of the second catalyst (here 0 mass %) and the third catalyst (here 42.6 mass %) was changed in each case.
[0040] The preparation of the membrane electrode assembly is generally carried out as follows:
[0041] First, separate dispersions ("inks") are prepared for the production of the anode and cathode catalyst layers by dispersing the corresponding catalyst, the proton-conducting ionomer and a suitable solvent (selected from water and organic solvents) with the aid of a suitable dispersing device. To produce the anode catalyst dispersion, a second catalyst and a third catalyst are used and their composition is varied in such a way that different ratios of platinum to non-platinum metal are achieved. The anode and cathode inks are then applied to a PTFE carrier foil and dried in order to produce anode and cathode layers having the desired weight per unit area (loading) relative to the platinum metal. The proton-conducting membrane is then arranged between the anode layer and the cathode layer located on the carrier foil and pressed under pressure and temperature in such a way that a transfer of the previously prepared electrode layer to the diaphragm occurs. Perfluorinated or hydrocarbon-based polymers functionalized with acid groups (e.g. sulfonic acid or carboxylic acid) can be used as ionomers. Here, the acid groups are usually arranged in side chains, whose chain lengths can vary and can exist as straight chains or branches. As organic solvents, alcohols, ketones, aldehydes, carboxylic acids, carboxylic acid esters, ethers or amides, or mixtures thereof, which each have different chain lengths and ring structures, can generally be used.
[0042] Anode 1 (Pt:Ru=9:1):
[0043] 7.00 g of a pure platinum catalyst consisting of 19.9% by mass of platinum and 80.1% by mass of a carbon support and 0.77 g of a platinum-ruthenium alloy catalyst consisting of 30.5% by mass of platinum, 23.6% by mass of ruthenium and 45.9% by mass of a carbon support were dispersed in a suitable dispersing apparatus for 1 hour together with 19.20 g of an ionomer dispersion consisting of 24.9% of a proton-conducting ionomer and 75.1% by mass of water and 73.03 g of a further solvent. The catalyst ink thus obtained was applied to a PTFE support foil and the wet layer thickness was set so as to obtain a wet layer thickness of between 0.015 mg / cm 2 With 0.2mg / cm 2 The weight per unit area in platinum is between .
[0044] Anode 2 (Pt:Ru=6:1):
[0045] 6.64 g of a pure platinum catalyst consisting of 19.9% by mass of platinum and 80.1% by mass of a carbon support and 1.19 g of a platinum-ruthenium alloy catalyst consisting of 30.5% by mass of platinum, 23.6% by mass of ruthenium and 45.9% by mass of a carbon support were dispersed in a suitable dispersing apparatus for 1 hour together with 18.88 g of an ionomer dispersion consisting of 24.9% of a proton-conducting ionomer and 75.1% by mass of water and 73.29 g of a further solvent. The catalyst ink thus obtained was applied to a PTFE support foil and the wet layer thickness was set so as to obtain a 1.5% to 2.5% ionomer dispersion of 0.015 mg / cm 2 With 0.2mg / cm 2 The weight per unit area in platinum is between .
[0046] Anode 3 (Pt:Ru=3:1):
[0047] 4.76 g of a pure platinum catalyst consisting of 19.9% by mass of platinum and 80.1% by mass of a carbon support and 2.34 g of a platinum-ruthenium alloy catalyst consisting of 30.5% by mass of platinum, 23.6% by mass of ruthenium and 45.9% by mass of a carbon support were dispersed in a suitable dispersing apparatus for 1 hour together with 15.62 g of an ionomer dispersion consisting of 24.9% by mass of a proton-conducting ionomer and 75.1% by mass of water and 77.27 g of a further solvent. The catalyst ink thus obtained was applied to a PTFE support foil and the wet layer thickness was set so as to obtain a wet layer thickness of between 0.015 mg / cm 2 With 0.2mg / cm 2 The weight per unit area in platinum is between .
[0048] cathode:
[0049] 6.67 g of a platinum-cobalt alloy catalyst consisting of 48.5% by mass of platinum, 4.9% by mass of cobalt and 46.6% by mass of a carbon support were dispersed together with 93.33 g of an ionomer dispersion consisting of 3.60% by mass of a proton-conducting ionomer and 96.4% by mass of water and further solvent in a suitable dispersing apparatus for 1 hour. The catalyst ink obtained in this way was applied to a PTFE support foil and the wet layer thickness was set so as to obtain a 0.4 mg / cm 2 The weight per unit area in platinum.
[0050] Preparation of electrode-diaphragm composite:
[0051] The supported anode and cathode catalyst layers were arranged overlappingly on opposite sides of the proton-conducting membrane and subsequently pressed in a press at a temperature of 160° C. for 5 minutes under pressure, so that a bond between electrode and separator was produced and the electrode could be removed from the corresponding PTFE support foil without residue.
[0052] The measurement parameters are as follows:
[0053] Power density and CO tolerance:
[0054] The cell voltage of the catalyst-coated membrane was first investigated by means of polarization curves without CO contamination. The cell temperature was 80° C., the gas temperature was 64° C., the humidity correspondingly 50% relative humidity. The prepressure at the gas inlet was 1.5 bar.
[0055] A hydrogen stream with 0.2 ppm CO was then enriched on the anode side and supplied to the anode with a 30 vol% nitrogen dilution. The power density was re-studied. -2 The reduction in cell voltage at a current density of 2.5 A is indicative of the CO tolerance of the catalyst-coated membrane.
[0056] Startup / Shutdown Cycle Test (SUSD)
[0057] In the gas switching experiment, the SUSD cycle is carried out with a residence time of the hydrogen / air boundary with a precise definition. For this purpose, the anode side is equipped with a three-way valve, which enables switching from dry air to moist hydrogen or vice versa. In order to simulate the start-up (Start-up), the anode flow area is first filled with dry air. Subsequently, it is switched to moist hydrogen, which results in the formation of a hydrogen-air boundary. In contrast, the anode flow area filled with hydrogen is flushed with air during the shutdown process (Shut-down), which results in the formation of an air-hydrogen boundary. Here, during the SUSD experiment, the operating conditions are kept constant in the two chambers (anode and cathode) of the cell (1.5 bar absolute pressure, inlet, cell temperature 35°C, gas temperature 30°C and 75% relative humidity). The residence time of the hydrogen-air boundary in the cell is defined by the volume of the flow area and the volume flow rate of the gas fed and is 0.3 seconds. The time between start-up and shutdown is set to 120 seconds. A total of 500 SUSD cycles are repeated.
[0058] Power density and CO tolerance after SUSD cycling:
[0059] The polarization curves were remeasured after the SUSD cycle. The decrease in the cell voltage relative to the first measurement was studied. The CO tolerance was then studied again similar to the above method.
[0060] As from Figure 2 As can be seen in the graph, the ratio of the total mass ratio of the platinum of the second catalyst and the platinum of the third catalyst to the total mass ratio of the metal (Ru) other than platinum of the second catalyst and the third catalyst varies in the range of about 10:1 to about 2:1. Five regions can be distinguished in terms of power stability and CO stability of the membrane electrode assembly: In region A, that is, when the mass ratio of Pt:Ru is greater than 9:1 and the anode load is low relative to the unit area weight of platinum, the CO tolerance is significantly reduced. In region E, that is, when the mass ratio of Pt:Ru is less than 3:1 and the anode load is high relative to the unit area weight of platinum, the long-term stability of the (catalytic) power of the membrane electrode assembly is significantly reduced. In regions B and D, good results were achieved for the long-term stability of the (catalytic) power and for CO tolerance, with the best results being obtained in region C.
[0061] Figure 3 The table in shows the Figure 2 The table shows the long-term stability of the (catalytic) power of the membrane electrode assembly or at 1.2 A cm -2 The cell voltage loss after 500 SUSD cycles at a current density of 1.3 Å is particularly evident for high Ru contents, i.e., for 0.2 mg cm -2For the combination of a high anode loading of 100 μm and a Pt:Ru mass ratio of 3:1, a significant cell voltage drop of more than 50 mV was observed.
[0062] Figure 4 The table in also shows the Figure 2 The table shows that good CO tolerance and power of the membrane electrode assembly are obtained at a Pt:Ru mass ratio in the range from 9:1 to 3:1, wherein at the extreme values of low Ru content, that is to say at very low anode loading and a Pt:Ru mass ratio of 9:1, these values already deteriorate significantly. By additionally varying the weight per unit area of Pt in the anode, the CO tolerance and power of the membrane electrode assembly can be further improved.
[0063] In addition to the above textual description of the invention, for the purpose of supplementary disclosure thereof, explicit reference is hereby made to the graphical illustrations of the invention in the accompanying drawings.
[0064] Reference numerals list
[0065] 1 Membrane Electrode Assembly
[0066] 2 Cathode
[0067] 3 Anode
[0068] 4 Proton conducting membrane
[0069] 5. First Catalyst
[0070] 6 Proton Conducting Ionomers
[0071] 7 Conductive carrier
[0072] 8 Proton Conducting Ionomers
[0073] 9 Second Catalyst
[0074] 10 The Third Catalyst
[0075] 11 Conductive carrier
Claims
1. A membrane electrode assembly (1), comprising a cathode (2), an anode (3) and a proton conducting membrane (4), wherein - the cathode (2) comprises a first metal-containing catalyst (5) and a proton-conducting ionomer (6), wherein The anode (3) comprises a proton-conducting ionomer (8), a second metal-containing catalyst (9) catalyzing the reaction of hydrogen to protons, and a third metal-containing catalyst (10) catalyzing the reaction of CO to CO2, wherein the ratio of the total mass ratio of the platinum of the second catalyst (9) and the platinum of the third catalyst (10) to the total mass ratio of the metal other than platinum of the second catalyst (9) and the third catalyst (10) is greater than 3:1 and less than or equal to 9:1, wherein the total unit area weight of the platinum of the second catalyst (9) and the platinum of the third catalyst (10) is less than 0.4 mg / cm 2 .
2. The membrane electrode assembly (1) according to claim 1, wherein the second catalyst (9) and the third catalyst (10) are respectively arranged on a conductive carrier (11).
3. The membrane electrode assembly (1) according to claim 1, wherein the second catalyst (9) is selected from platinum, and the third catalyst (10) is selected from: alloys, metals, metal oxides or mixtures of these substances.
4. The membrane electrode assembly (1) according to claim 3, wherein the alloy comprises an alloy of platinum and at least one element selected from the group consisting of Ru, Rh, Ni, Cu and Ir.
5. The membrane electrode assembly (1) according to claim 2, wherein the conductive support (11) is selected from conductive carbon, inorganic oxides and mixtures thereof, and / or wherein the conductive support (11) has a molecular weight of 50 to 1000 m 2 / g specific surface area.
6. The membrane electrode assembly (1) according to any one of claims 1 to 4, wherein the weight per unit area of platinum of the second catalyst (9) is less than 0.3 mg / cm 2 , and / or wherein the total unit area weight of the platinum of the second catalyst (9) and the platinum of the third catalyst (10) is greater than 0.015 mg / cm 2 , and / or wherein the weight per unit area of platinum in the second catalyst (9) is greater than 0.015 mg / cm 2 .
7. The membrane electrode assembly (1) according to claim 6, wherein the total unit area weight of the platinum of the second catalyst (9) and the platinum of the third catalyst (10) is greater than 0.03 mg / cm 2 .
8. The membrane electrode assembly (1) according to claim 6, wherein the weight per unit area of platinum in the second catalyst (9) is greater than 0.03 mg / cm 2 .
9. The membrane electrode assembly (1) according to any one of claims 1 to 4, wherein the mass ratio of the platinum of the first catalyst (5) to the total mass ratio of the metals other than platinum of the second catalyst (9) and the third catalyst (10) is greater than 12:
1.
10. The membrane electrode assembly (1) according to any one of claims 1 to 4, wherein the mass ratio of the platinum of the first catalyst (5) to the total mass ratio of the metals other than platinum of the second catalyst (9) and the third catalyst (10) is greater than 35:
1.
11. The membrane electrode assembly (1) according to any one of claims 1 to 4, wherein the first catalyst (5) is selected from platinum, platinum alloys, transition metals, transition metal alloys and mixtures thereof, and / or wherein the first catalyst (5) is arranged on a conductive carrier (7).
12. The membrane electrode assembly (1) according to claim 11, wherein the transition metal is cobalt or nickel.
13. The membrane electrode assembly (1) according to any one of claims 1 to 4, wherein the membrane is selected from the group of perfluorinated, partially fluorinated or non-fluorinated materials and / or wherein the membrane has a layer thickness of 3 to 20 μm.
14. A fuel cell comprising a membrane electrode assembly (1) according to any one of claims 1 to 13.
Citation Information
Patent Citations
Electrode
US5795669A